Productivity, cost and product quality of complete-tree processing in orchard termination operations - Assirelli, A.; Brambilla, M.; Leonello, E. C. [UNESP]; Magagnotti, N.; Spinelli, R. (Elsevier, 2022)
To minimize the burden on periodical orchard termination and renewal, complete tree removal and processing represent the most effective work technique, when the above- and below-ground tree portions are kept together and removed in one single action. However, the presence of rootstocks imposes specific biomass processing techniques, when turning the removals into wood fuel. In particular, one needs to use a comminuting machine that can cope with soild contamination and introduce a cleaning step to remove soil particles from the feedstock. The goal of this research was to determine if one can efficiently process complete trees arising from orchard termination conducted as an integrated single-pass operation. The processing system under testing consisted of a commercial set-up commonly used when producing compost at recycle yards and was obtained by coupling a slow-speed shredder with a rotary sieve in an on-line arrangement. Productivity levels were quite stable, varying between 17 and 24 tPMH−1. Total system cost was 304 € per scheduled machine hour (SMH) and processing cost ranged from 18 to 25 €t−1. 82% of the input material ended into the fuelwood stream, which still contained some residual contamination estimated at 7% (close enough to the ash content of orchard pruning residues). Therefore, the cost of orchard termination and disposal is reduced, and an additional fuel stream can be captured and directed towards the expanding bioenergy sector. Combined shredding and screening represents a further example of integration and is essential to the efficient upgrading of complete tree material into a viable fuel.
Keywords: Bioeconomy; Bioenergy; Biomass; Contamination; Woodfuel quality